Santorini : Volcano, Natural History, Mythology - Friedrich, Walter L. (Vide Verden, 2009)
Front Matter; Front Cover; Title Page; Copyright Page; Contents; Preface; Acknowledgements; Introduction; I The geological framework; 1 The geography of Santorini; Thera - the main island of Santorini; Therasia - the Little Thera; Aspronisi - the White Island; The Kameni Islands; The Caldera - the large central basin; Kolumbos - the invisible volcano; The Christiana Islands - relatives of the Santorini volcanic group; An island with deep roots in history; 2 Santorini and plate tectonics; Continental drift and Plate tectonics; Geology of the Aegean region